2017
DOI: 10.3389/fbuil.2017.00042
|View full text |Cite
|
Sign up to set email alerts
|

Multi-lane Roundabout Capacity Evaluation

Abstract: Although two-lane roundabouts theoretically exhibit excellent operating performance, in practice, safety problems arise because of inappropriate driving behavior. Turbo roundabouts, which are characterized by a much higher level of safety, are alternatives to classic two-lane roundabouts, but the capacity-related benefits derived from such roundabouts remain an open issue. Accordingly, this study uses an equilibrium traffic flow allocation approach to evaluate multi-lane roundabout capacity based on gap accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The correction factor α of the influence of an existing flow was substituted by two parameters a 1 and a 2 . This model allows a capacity calculation for different legs in various types of turbo-roundabouts, and it has been used, for example, in case studies of the transformation of a standard roundabout into a turboroundabout [10][11][12][13]. According to the Fortuijn-Harte model, the single-lane capacity of a minor entry is given by the following equation: Brilon capacity model [14] is based on the Tanner´s basic idea [5] as well as the Wu model.…”
Section: Capacity Models For a Single-lane Minor Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…The correction factor α of the influence of an existing flow was substituted by two parameters a 1 and a 2 . This model allows a capacity calculation for different legs in various types of turbo-roundabouts, and it has been used, for example, in case studies of the transformation of a standard roundabout into a turboroundabout [10][11][12][13]. According to the Fortuijn-Harte model, the single-lane capacity of a minor entry is given by the following equation: Brilon capacity model [14] is based on the Tanner´s basic idea [5] as well as the Wu model.…”
Section: Capacity Models For a Single-lane Minor Entrymentioning
confidence: 99%
“…The Hagring capacity model, considering traffic flow allocation into two circulatory lanes, has been used with some simplifications in several capacity studies of turbo-roundabouts: [13,[17][18][19][20][21]. Two of them used different critical headway values t c,i and t c,e to estimate the left-lane capacity of two-lane turbo-roundabout minor entries [17,18].…”
Section: Capacity Models For a Single-lane Minor Entrymentioning
confidence: 99%
“…e authors concluded that the overall capacity of basic turbo roundabouts is superior to conventional two-lane roundabout's capacity under any circumstances. Finally, the authors added that minor approaches' capacity of turbo roundabouts is boosted as well [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process of gap acceptance is one of the most commonly used techniques for capacity calculation at roundabouts [1][2][3]. It is based on gaps/ lags that are accepted and rejected by drivers from lower priority approaches.…”
Section: Introductionmentioning
confidence: 99%